PENGARUH MODEL PROBLEM BASED LEARNING BERBASIS ETNOMATEMATIKA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS IX MTs N 1 MERANGIN - Gebi Yulisa Putri; Hidayati Rais; Hasmawati (Matedukasia, 2024)
This research was motivated by the students' low mathematics problem-solving abilities. There are 5 five indicators of 9 mathematical problem solving abilities that students have not been able to achieve. One of the reasons is that there are still many students who are not active in the learning process and there is a lack of variety in the learning strategies used by teachers. This research aims to describe mathematical problem solving abilities using a Problem Based Learning model based on ethnomathematics compared to conventional learning for class IX students at MTs N01 Merangin Year 3 Lesson 2023/2024. The method used in this research uses an experimental method and the population is all students in class IX MTs N 1 Merangind for the 2023/2024 academic year, totaling 182 people. The sampling technique uses Simple Random Sampling. The samples selected were Class IX C as = Experimental Class and Class 5 IX D as Control Class. The method for analyzing data before conducting a hypothesis test is tested first with a normality test and a harmony test, where it is known that the data is normally distributed and has homogeneous variance, so the hypothesis is tested with the t-test. The average score obtained from data analysis for the experimental class was 53.68, variance 39.0250, while the control class obtained an average score of 49.10, variance 68.1780. The results of the hypothesis test were obtained, tcount = 2.373 and ttable = 1.671. Because tcount > ttable, H0 was rejected and H1 was accepted. The conclusion of this research is that the ability to solve mathematical problems using the Ethnomathematics-based Problem Based Learning model is better than using conventional learning for class IX students at MTs N 1 Merangin for the 2023/20 academic year